Myanmar's Rejection Of The United Nations Resolution: Allowed of Not? - Yordan Gunawan; Debby Kemira Putri Drajat; Dela Rinanda Putri; Verocha Jayustin Sastra (Universitas Tidar, 2023)
Myanmar's Ministry of Foreign Affairs rejected the Myanmar Ministry of Foreign Affairs calls for an arms embargo and power struggle by the military in a UN general assembly resolution last February because the resolution was considered based on unilateral accusations and false assumptions, and the resolution was deemed not legally binding. In addition, several Myanmar statements have been adopted by the UN security council, which has the authority as well as resolutions deemed legally binding, such as the prohibition of acts of violence against protesters. In addition, the resolution calls on the military not to commit acts of violence as well as restore the democratic transition. The purpose of this study is to find out whether Myanmar may reject the UN General Assembly resolution or not. The study uses normative legal research with a case approach using qualitative descriptive methods to describe the legal reasons used in Myanmar's rejection of the UN General Assembly resolution and how to apply the principle of pacta sunt servanda in this case. The results show that Myanmar rejects the UN resolution calling for an arms embargo because Myanmar considers that the resolution is not legally binding and based on the pacta sunt servanda. Myanmar should accept the UN General Assembly resolution because it binds an agreement to the parties who made it.